1-O-Alkylglycerol Ethers from the Marine Sponge Guitarra abbotti and Their Cytotoxic Activity - Sergey A. Dyshlovoy; Sergey N. Fedorov; Vasily I. Svetashev; Tatiana N. Makarieva; Anatoliy I. Kalinovsky; Olga P. Moiseenko; Vladimir B. Krasokhin; Larisa K. Shubina; Alla G. Guzii; Gunhild von Amsberg; Valentin A. Stonik (Marine Drugs, 2022)
The cytotoxicity-bioassay-guided fractionation of the ethanol extract from the marine sponge Guitarra abbotti, whose 1-O-alkyl-sn-glycerol ethers (AGEs) have not been investigated so far, led to the isolation of a complex lipid fraction containing, along with previously known compounds, six new lipids of the AGE type. The composition of the AGE fraction as well as the structures of 6 new and 22 previously known compounds were established using 1H and 13C NMR, GC/MS, and chemical conversion methods. The new AGEs were identified as: 1-O-(Z-docos-15-enyl)-sn-glycerol (1), 1-O-(Z-docos-17-enyl)-sn-glycerol (2), 1-O-(Z-tricos-15-enyl)-sn-glycerol (3), 1-O-(Z-tricos-16-enyl)-sn-glycerol (4), 1-O-(Z-tricos-17-enyl)-sn-glycerol (5), and 1-O-(Z-tetracos-15-enyl)-sn-glycerol (6). The isolated AGEs show weak cytotoxic activity in THP-1, HL-60, HeLa, DLD-1, SNU C4, SK-MEL-28, and MDA-MB-231 human cancer cells. A further cytotoxicity analysis in JB6 P+ Cl41 cells bearing mutated MAP kinase genes revealed that ERK2 and JNK1 play a cytoprotective role in the cellular response to the AGE-induced cytotoxic effects.